Correlation Between Arthritis And Independent Activities Of Daily Living (ADL) In Elderly - Yuliana; Wahyu Sulfian; Elifa Ihda Rahmayanti (Journal of sciences and health, 2022)
Baground: The incidence of Arthritis in the elderly affects the daily activities of the elderly, decreased body functions which can cause the elderly to experience a decrease in independence in carrying out Activities Of Daily Living (ADL). Method: This research have  correlation method with Cross Sectional design. The population is total elderly in Sumbersari PHC and sampling about 95 respondents that taken by Purposive Sampling technique. The result of  research found that elderly with Arthritis about 59 respondents (62,1%) and non Arthritis about 36 respondents (37,9%), reducing of activities independently about 40 respondents (42,1%), independent category and 55 repondents (57,9%) have dependent category. Results: Bivariate analyses result by Chi-Squaretest found that have correlation between Arthritis with activities independently toward elderly in Sumbersari PHC with p value =0,000, (P<0,05). Conclusions: Conclusion of research mentioned that have correlation of Arthritis with Activities Of Daily Living toward elderly in Sumbersari Phreagrding C. The PHC shoul provide the know ledge regarding Arthritis and examintaion about activities independently toward elderly.  Keywords: Arthriti, activities independently